Implementasi Peraturan Daerah Kabupaten Merangin Nomor 3 Tahun 2014 Tentang Penataan Pedagang Kaki Lima: (Implementation of Merangin Regency Regional Regulation Number 3 of 2014 Concerning The Arrangement of Street Vendors) - Joko Susanto; Fajar Ifan Dolly; Rival Hardianto; Zepa Anggraini; M. Chotib (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2026)
In Merangin Regency, the economic and trade center is divided into two areas: Pasar Atas Bangko and Pasar Bawah Bangko. In this study, the author focuses on Pasar Bawah Bangko as the object of research. In the business activities of street vendors in the Pasar Bawah Bangko area, many street vendors still sell in prohibited areas such as public places, roadsides, sidewalks, and street vendors. This is difficult to regulate due to a lack of awareness of the impact and consequences of their actions. This research method uses a descriptive method with a qualitative approach. The population in this study were all employees of the Bungo Public Order Agency (Satpol PP), all street vendors in the Pasar Bawah Bangko area, and the community living in the Pasar Bawah Bangko area. The number of analysis units in this study was 10 people, determined using purposive sampling. Data collection techniques used in this study included observation, documentation, and interviews. The results of this study indicate that the Implementation of Merangin The results of this study indicate that the Implementation of Merangin Regency Regional Regulation Number 3 of 2014 Concerning the Arrangement of Street Vendors has been realized, although in its realization it is still not optimal, because there are still several obstacles such as, limited information received by street vendors, and there are still street vendors who do not obey the rules in the Pasar Bawah Bangko area. To overcome these obstacles, the Merangin Regency Government through the Merangin Regency Civil Service Police Unit made efforts in the form of giving written warning letters to street vendors, dismantling or closing business premises and providing special areas for street vendors.